Orientation to Happiness as a Predictor of University Students’ Engagement - Maria Fernanda Durón-Ramos; Fernanda García Vázquez (International Journal of Evaluation and Research in Education (IJERE), 2018)
There is empirical evidence for a close link between positive personal components and students' engagement in academic activities. Personal well-being is a construct that can be studied from a variety of angles. Recent studies point to the relevance of orientation to happiness examining three types of well-being. The main objective of this study is to test the relationship that orientation to happiness has with university students' engagement at a public institution in northern Mexico. A stratified probabilistic sample of 266 students was used. The internal consistency of the scales was analyzed using the SPSS package and a model of structural equations in the EQS program. Results indicate is a direct and significant relationship between the orientation to happiness and the students' engagement. This supports the importance of promoting positive factors in students to improve their academic and personal development.